Features of metabolic reactions to various water-salt loads in female rats - Gozhenko, Anatoliy I; Zavidnyuk, Yuriy V; Sydliaruk, Nataliya I; Mysula, Igor R; Klishch, Ivan M; Zukow, Walery; Popovych, Igor L; Korda, Mykhaylo M (Journal of Education, Health and Sport, 2018)
Background. In the previous article we reported that screening registered parameters of water-salt, nitrous and lipid metabolism as well as the neuroendocrine-immune complex found 42 among them who in rats subjected to various water-salt loads, significantly different from that of intact rats, but on average the same group of animals that received liquids with different mineralization and chemical composition. The purpose of this article is to find out the features of the reactions of the parameters of metabolism. Materials and methods. Experiment was performed on 58 healthy female Wistar rats 240-290 g divided into 6 groups. Animals of the first group remained intact, using tap water from drinking ad libitum. Instead, the other rats received the same tap water as well as waters Sophiya, Naftussya, Gertsa and its artificial salt analogue through the probe at a dose of 1,5 mL/100 g of body mass for 6 days. The day after the completion of the drinking course in all rats the parameters of water-salt, nitrous and lipid metabolism were registered. Results. Found that 16 metabolic parameters the maximum deviates from the level of intact rats under the influence of the salt analogue of Gertsa water, a smaller, but tangible effect is made by the Gertsa native water, even less effective waters Sofiya and Naftussya, instead of ordinary water is almost ineffective in relation to these metabolic parameters. The other 19 parameters deviates to a maximum extent from the reference level after the use of water Naftussya, fresh water is less effective, whereas quasi-isotonic liquids are practically inactive for these parameters. The remaining 13 parameters in animals that use normal water, deviates from intact control to the same extent as in the previous pattern, which, apparently, is also due to the stressful effects of the load course. Both Naftussya and Gertsa water and its salt analogue prevent the stress deviations of these parameters. Instead, by consumption of water Sofiya stresses deviations of these parameters is reversed. The method of discriminant analysis revealed 33 variables (among them 8 refer to plasma/erythrocytes electrolytes, 7 to electrolytes of urine, to other metabolic parameters of plasma 5 and urine 9, as well as glomerular filtration, canalicular reabsorption, diurese and urine osmolarity), the totality of which the metabolic reactions to various water-salt loads are identified (recognized) with an accuracy of 98,3%. Conclusion. The features of the reactions of the parameters of metabolism are due to the content in waters NaCl, SO42- as well as organic carbon and nitrogen.